Efforts to Preserve the Value of Mutual Cooperation in the Jorong Lubuak Limpato Nagari Tarantang Community, Harau District, 50 City Regency - Ade Kurnia; Giva Aprilia Hendriza (MultiTech Publisher, 2025)
Mutual coopeartion means working together to achieve a desired result. The factors behind the waning of mutual cooperation behavior are as follows: 1. Lack of awareness of the importance of mutual cooperation 2. Lack of participation of elements or layers of society 3. The emergence of a culture of individualism and materialism that has penetrated rural areas has begun to fade the values of mutual coopeartion so that the mutual cooperation is not running well This type of research is qualitative research, which is a research process to understand human or social phenomena by creating a comprehensive and complex picture that can be presented in words, reporting detailed views obtained from informant sources, and conducted in a natural setting. With the existence of mutual cooperation, there should be a value of sincerity which is the nature of helping without expecting a return and creating a value of unity that creates a close relationship between communities. The existence of a wage/salary system is also a factor in the shift in the values of mutual cooperation.